EM TEMPOS DE GLOBALIZAÇÃO, QUE DE NOVO SE ENUNCIA? - Cardoso, Silvia Helena Barbi (Organon, 2002)
This paper shows how the concern with Discourse Analysiscan be combined with broader problems of social nature. The aim is toquestion whether there is a new significant discourse besides the one belongingto the reigning neoliberal ideology. Our hypothesis is that totalhegemony does not exist - nowadays it is possible to find significant heterogeneityamong discourses which apparently are not so important anddo not apparently constitute themselves as a political challenge to globalizationor neoliberal system, such us the one belonging to the revolutionarymovement of peasants in Brazil, or even the one belonging to theInternational Social Forum. On the track of these new discourses, twodocuments of linguistic politics are brought to discussion: Universal Declarationof Linguistic Rights and a Brazilian project of law.